STRATIGRAPHICAL SIGNIFICANCE OF THE PLEISTOCENE SPERMOPHILINI IN THE LIGHT OF THEIR EVOLUTION PECULIARITIES - POPOVA, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main evolutionary steps of the Pleistocene Spermophilus have been reconstructed on the base of the spatial-karyotypic model. Potentialities of stratigraphical using of their fossil remains have been grounded.